investigation of the effects of ion channel expression in infertile men patients - Carkci, S.; Karakeci, A.; Onalan, E.; Ozan, T.; Firdolas, F.; Pirincci, N.; Orhan, I. (Oxford Univ Press, 2016)
[Abstract Not Available]